(untitled) (World Economics and Finance Bulletin, 2024)
The purpose of the current research is to reveal the role of internal digital audit procedures represented in (planning the audit process, assessing risks, examining and evaluating the internal control system, and implementing analytical procedures for information) to reduce creative accounting used for financial fraud by (motives for using creative accounting, creative accounting practices, and mechanisms for detecting creative accounting) among a sample of accountants in Iraqi commercial banks. In order to address the research problem of what is the role of internal digital audit procedures in reducing creative accounting used for financial fraud in commercial banks in the province of Baghdad, The research resorted to the use of the questionnaire tool in order to measure the level of availability of research variables in commercial banks, and on the basis of that was the use of a sample of (109) accountant, and to analyze the research data, two packages were used to come up with accurate results represented in (SPSS&AMOS). V.28), has included statistical methods in (arithmetic mean, standard deviation, deviation coefficient, Cronbach alpha stability coefficient, correlation coefficient, and regression coefficient) The research came out with several results, foremost of which was that the use of internal digital audit procedures in commercial banks contributes to reducing financial fraud used in creative accounting, which provides effective tools to detect manipulation and forgery in financial data and statements.